Modeling The Microrelief Structure of Ti6Al4V Titanium Alloy Surface After Exposure to Femtosecond Laser Pulses - Lytvynenko, Iaroslav; Maruschak, Pavlo; Seitz, Hermann; Schnell, Georg (International Journal of Integrated Engineering, 2022)
A method of mathematical modeling of the ordered surface relief of titanium alloy Ti6Al4V after femtosecond laser treatment is proposed, which allowed obtaining the informative signs of the self-organized surface irregularities, taking into account the stochastic and cyclic nature of this process. An algorithm has been developed, and a package of computer programs has been created based on the proposed mathematical model. These methods make it possible to analyze the zone-spatial two-dimensional structure of the cyclic relief of the modified surface. They are also the basis for creating the specialized software for the automated profilometric diagnostic systems.